Applying Zachman Framework in Developing Digital Blueprint in Plantation Company - Rahmat Ivan Aziz, Andi Ali Zainal Abidin, Gunawan Wang, Nilo Legowo (International Journal of Control and Automation, 2020)
Digital Blueprint is an organizational governance document that contains guidelines for information system needs and planning in implementing and building information systems. Plantation Company is one of the companies that view the creation of Digital Blueprint as needed to realize the company’s vision and mission in developing and implementing IS / IT. This study aims to create enterprise architecture, IS / IT strategic planning in Plantation Companies in the form of Digital Blueprint using the Zachman Framework. The research method carried out is by defining enterprise architecture in the form of business architecture, data architecture, application architecture, and technology architecture. The results of this research are in the form of a Digital Blueprint that uses 3x3 Zachman matrix cells which are expected to help companies to develop business processes and be able to store in detail the design assets from various points of view, thus helping companies in development.